Striking a balance: Managing El Niño and La Niña in Myanmar’s agriculture - Sutton, William R.; Srivastava, Jitendra P.; Rosegrant, Mark W.; Thurlow, James; Vasileiou, Ioannis (World Bank, 2019)
This report’s aim is to raise awareness on El Niño–Southern Oscillation (ENSO) events among Myanmar’s policy makers and stakeholders. Particularly, the aim is to guide them on preparedness and resiliency building measures. It does this by providing information on ENSO’s social, poverty, economic, and agricultural impacts in Myanmar and outlining ways forward. The report finds that ENSO’s impacts vary from region to region but tend to exacerbate current climatic trends. Myanmar’s government attempted to prepare for, and respond to, the 2016 El Niño, but capacity andorganizational constraints limited its effectiveness. Preparing for ENSO is important because of Myanmar’s low resilience to climate shocks, the importance of agriculture for the national economy, the rural and poor populations’ climate vulnerability, and the lack of research on ENSO in Myanmar.